The Impact of Orofacial Harmonization on the Quality of Life of Dental Patients: A Longitudinal Clinical Study (International Seven Journal of Multidisciplinary, 2023)
This longitudinal clinical study investigates the impact of orofacial harmonization (OFH) on the oral health-related quality of life (OHRQoL) of dental patients. While traditional dentistry focuses on functional and dental aesthetics, OFH integrates various procedures, such as botulinum toxin and dermal fillers, to achieve a more balanced facial appearance. The study aims to fill a gap in the literature by systematically assessing the subjective benefits of these treatments. A cohort of patients will be followed over a 12-month period, with data collected using validated patient-reported outcome measures, including the Oral Health Impact Profile (OHIP), at baseline, 3, 6, and 12 months post-treatment. We hypothesize that OFH procedures will lead to a significant and sustained improvement in patients' OHRQoL, particularly in psychosocial and functional domains. The findings will provide empirical evidence for the therapeutic value of OFH, contributing to the development of patient-centered treatment protocols and re-establishing these procedures as an integral part of holistic dental care.